Design of Marketing Strategy Using Quantitative Strategic Planning Matrix (QSPM) Method in DW Ice Cream MSMEs to Increase Sales - Muhammad Fiqri Aprilian Adriansyah; Maria Dellarosawati I.; Isnaeni Yuli A. (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
To formulate alternative strategies, this Final Project analyzes internal factors using internal audit and external factors using PEST analysis and Porter's Five Force analysis to be able to fill the IFE and EFE matrices. The IFE and EFE matrices will be input to the IE matrix to determine the position of MSMEs and the SWOT matrix to find out alternative strategies such as how that can be applied to MSMEs. Then use the QSPM matrix to select priorities from the alternative strategies obtained. The final step of this Final Project is to develop a Strategy Roadmap to find out the implementation plan and the things that need to be prepared in implementing the chosen strategy. The results of the calculation produce a value of 2.54 for the IFE matrix and 2.4 for the EFE matrix which is the input to the IE matrix. The IE matrix determines the position of MSMEs in quadrant 5 (Hold and Maintain) with its strategy of market penetration and product development. From the IE matrix, it becomes the input to the SWOT matrix to formulate strategies according to the Hold and Maintain category which produces 14 alternative strategies. Furthermore, the 14 alternative strategies are selected which are in accordance with the existing conditions and the priority is determined on the QSPM matrix and then the strategy is chosen according to the QSPM, namely market penetration with a TAS value of 7.14. Furthermore, the product development strategy and the strategy to find investors received TAS scores of 4.74 and 3.93, respectively. The description of the selected strategy according to the QSPM is then compiled in the Strategy Roadmap based on 2 stages, namely the “strength improvement and development stage” and the “growth and expansion stage” whose implementation will be planned for 2 years. The strategy of market penetration, product development, and finding investors based on the analysis of internal and external factors of MSMEs is in accordance with the resources and limitations they have, which is expected to be useful for MSMEs to be able to increase sales figures and also to maintain the competitive advantage of DW Ice Cream.